O sentido da religiosidade/espiritualidade na vida da pessoa idosa institucionalizada - Moreira, Deiglis Alves (2020)
Old age is a natural process characterized by changes in biological, psychological and social aspects, with significant repercussions on life events and on its existence. Religiosity is the belief with practices related to some religious institution, related to the collective and spirituality involves a feeling of greater well-being, when we dive into the depth of ourselves, transmitting vitality and meaning to the moments of life. Religiosity / spirituality is part of the history, culture, formation and maintenance of bonds of the elderly, connects to the sacred, transcendent, mystical and the collective promoting the increase of faith and resilience. In this understanding, religiosity / spirituality can help the elderly person to better understand and experience the process of institutionalization, facing adversity, as well as giving meaning to life. The general objective of this study was to analyze the meaning of religiosity / spirituality in the lives of institutionalized elderly people. In response to the objective, this dissertation presents two productions. The first scientific production aimed to verify how much religiosity / spirituality gives meaning to life and strength to face life's difficulties. Cross-sectional study with 122 elderly people out of a total of 478, residing in long-term care facilities for the elderly, in municipalities in southern Brazil. Individuals aged 60 years or over, of both sexes, were included, cognition preserved according to the minimum scores of the mini mental state exam considering schooling. Most institutionalized elderly are adepts of religion. We have a predominance of white, marital status without a partner, schooling from 1 to 8 years and the elderly, in an expressive way, receive visits from family, friends and acquaintances. In long-lived elderly, spirituality and religiosity are essential, they value beliefs, using them in their religious practices, in facing daily difficulties, finding meaning and strength to overcome them. The second scientific production aimed to analyze and systematize the scientific production related to the theme of spirituality and old age in the period from 2010 to 2019, an integrative literature review, carried out in the Medline / Pubmed, Capes and Google Acadêmico databases, selecting 15 articles that composed the study sample. The results were compiled into three main categories: tools and validation of instruments to assess spirituality; spirituality, old age and suffering; spiritual well-being and self-transcendence. Religiosity / spirituality has a positive impact on the health of the elderly, their religious and spiritual beliefs and practices give strength to face the difficulties of life and promote existential meaning and meaning, being a strategy for institutionalized elderly for health care relationships. It is recommended that long-term care facilities for the elderly reflect and incorporate religiosity / spirituality in health practices.